Language and Culture Backgrounds of Mothers and Child Development: A Nationwide Study on the Incidence of Developmental Delays in Children Born to Immigrant Mothers in Taiwan - Tseng, Yen-Cheng; Lai, Der-Chung; Guo, How-Ran (Frontiers in Public Health, 2021)
Background: Transnational marriages are common as a result of globalization, and immigrant mothers face various degrees of differences in language and culture backgrounds. Mothers have great influences on the development of their children, but the effects of immigrant mothers’ language and culture backgrounds on developmental delays (DD) are seldom studied. To evaluate the potential effects of immigrant mothers’ language and culture backgrounds on DD of their children, we conducted a nationwide study in Taiwan. Methods: We analyzed the data from the national registry of DD in Taiwan from 2010 to 2013 and compared the incidence of DD in young children born to mothers from China, Vietnam, and Indonesia, where most of the immigrant mothers in Taiwan come from. Amongst the three countries, China is the closest to Taiwan in terms of language and culture, followed by Vietnam, and then Indonesia. Results: We identified 4604 patients of DD in 493081 children under 7 years old. The incidence rates showed an increasing trend among children born to mothers from China, Vietnam, and Indonesia (p < 0.01 in all years). Using children born to mothers from Vietnam, whose incidence rate of DD was in the middle amongst the three groups, as the reference, we found the incidence rate ratios in children born to mothers from China ranged from 0.65 to 0.73, and those in children born to mothers from Indonesia ranged from 1.04 to 1.26. Conclusions: The findings support the important role of mothers’ language and culture backgrounds in the development of children.